2021
DOI: 10.3389/fped.2021.664702
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Protective Factors Associated With Mental Health Symptoms During COVID-19 Home Confinement in Italian Children and Adolescents: The #Understandingkids Study

Abstract: Objective: To identify risk and protective factors for mental health symptoms associated with lifestyle changes caused by home confinement in pediatric subjects and in children and adolescents with a neuropsychiatric disorder.Study design: This was a prospective, cross-sectional study conducted from May 10 to May 31, 2020. Two online anonymous surveys were developed: population-based and clinical-based (children with neuropsychiatric disorders). Outcomes included emotional and behavioral symptoms, as assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 20 publications
0
38
0
3
Order By: Relevance
“…Despite these challenges, higher levels of social support have been consistently associated with better mental health outcomes during the pandemic. Lower levels of depression and anxiety symptoms have been observed in adults who report higher levels of social support ( Grey et al, 2020 ; Özmete & Pak, 2020 ) and in children and adolescents who reported higher levels of social connectedness and spent more time talking to others during the early phase of the pandemic ( Magson et al, 2021 ; Oliva et al, 2021 ). A stress buffering role of social support has also been reported in several studies during the pandemic.…”
Section: Stress Bufferingmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these challenges, higher levels of social support have been consistently associated with better mental health outcomes during the pandemic. Lower levels of depression and anxiety symptoms have been observed in adults who report higher levels of social support ( Grey et al, 2020 ; Özmete & Pak, 2020 ) and in children and adolescents who reported higher levels of social connectedness and spent more time talking to others during the early phase of the pandemic ( Magson et al, 2021 ; Oliva et al, 2021 ). A stress buffering role of social support has also been reported in several studies during the pandemic.…”
Section: Stress Bufferingmentioning
confidence: 99%
“…Parental support, in particular, has emerged as an important protective factor for both youths and young adults. The association of pandemic-related stressors with internalizing and externalizing problems was lower in young adults who experienced higher levels of parental support and had lower levels of parent-child conflict prior to the pandemic ( Skinner et al, 2021 ) and in children and adolescents who spent more time with their parents ( Oliva et al, 2021 ), who experienced lower conflict with parents ( Qu et al, 2021 ), and whose parents used more emotion coaching strategies ( Cohodes et al, 2021 ). Together these studies suggest that social support and connection are important protective factors that have the potential to facilitate resilience during the pandemic.…”
Section: Stress Bufferingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is now mounting evidence of persisting symptoms in children following acute Sars-Cov-2 infection, which has been named Long COVID, and studies that highlight how lifestyle changes during the COVID-19 pandemic have had a significant psychological impact on the pediatric population ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lockdown measures had an unfavorable impact on adolescents and young adults, and a large amount of literature highlighted a greater risk for the occurrence of psychiatric symptoms due to a change in their lifestyles and habits ( 11 ) as well as lower levels of post-traumatic growth ( 12 ). For instance, the closure of schools has imposed distance learning as an alternative to maintain continuity in the education of children and adolescents ( 13 ). The subsequent prolonged social isolation threatened the psycho-physical wellbeing of youths, worsening or unmasking psychopathology ( 14 ).…”
Section: Introductionmentioning
confidence: 99%